Safety and efficacy of sofosbuvir-velpatasvir to treat chronic hepatitis C virus infection in treatment-naive patients in Rwanda (SHARED-3): a single-arm trial. (June 2022) - Kateera, Fredrick; Shumbusho, Fabienne; Manirambona, Linda; Kabihizi, Jules; Murangwa, Anthere; Serumondo, Janvier; Makuza, Jean Damascene; Nsanzimana, Sabin; Muvunyi, Claude Mambo; Kabakambira, Jean Damascene; Sylvain, Habarurema; Camus, Gregory; et al.
Summary: Background: Hepatitis C virus (HCV) genotype 4 is the predominant type of HCV found in sub-Saharan Africa. Various genotype 4 subtypes, such as 4r, frequently have resistance-associated substitutions that can increase rates of treatment failure with common direct-acting antiviral regimens. In-vitro studies suggest that the NS5A inhibitor velpatasvir is effective against viral isolates containing such resistance-associated substitutions, but its clinical efficacy against genotype 4 non-a/d subtypes in sub-Saharan Africa remains to be confirmed. We aimed to evaluate the safety and efficacy of sofosbuvir–velpatasvir among adults chronically infected with HCV and naive to direct-acting antiviral treatment in Rwanda, where genotype 4 non-a/d subtypes predominate. Methods: In this single-arm prospective trial, we enrolled adults (age ≥18 years) in Rwanda who had chronic HCV infection and a plasma HCV RNA titre of at least 1000 IU/mL. Patients were referred from hospitals with HCV treatment programmes throughout Rwanda and were sequentially enrolled and assessed for eligibility at a single study site. Individuals with decompensated liver disease or hepatitis B virus co-infection were excluded. Participants were given an oral fixed-dose combination tablet of sofosbuvir (400 mg) and velpatasvir (100 mg) once-daily for 12 weeks. The primary endpoint was the proportion of participants with a sustained virological response 12 weeks after completion of treatment (SVR12) in the intention-to-treat population. Viral sequencing of the NS5A and NS5B genes was done at baseline for all participants and end of follow-up (week 24) for participants who did not have SVR12. This study is registered with ClinicalTrials.gov (NCT03888729 ) and is completed. Findings: Between Sept 23, 2019, and Jan 10, 2020, 73 individuals were screened for eligibility, of whom 12 (16%) were excluded and 61 (84%) were enrolled. 40 (66%) participants were female, 21 (34%) were male, median age was 64 years (IQR 51–74), and median baseline HCV viral load was 5·7 log10 IU/mL (5·2–6·2). The genotypes identified among the participants were 4k (28 [46%] participants), 4r (11 [18%]), 4v (eight [13%]), 4q (five [8%]), 4l (three [5%]), 4b (one [2%]), 4c (one [2%]), and one undetermined genotype 4 subtype. Three isolates could not be sequenced and were of indeterminate genotype. Of the 55 HCV isolates that were successfully sequenced, all had at least two NS5A resistance-associated substitutions. 59 (97% [95% CI 89–99]) participants had SVR12. 18 (30%) participants had grade 3 adverse events (including 12 [20%] with hypertension), and none had grade 4 adverse events. Four (7%) participants had serious adverse events, including one asthma exacerbation, one abscess, one uterine myoma, and one pelvic fracture related to a motor vehicle accident. No serious adverse events were attributed to the study drug and no adverse event resulted in discontinuation of the study drug. Interpretation: A 12-week regimen of sofosbuvir–velpatasvir is safe and efficacious in treating chronic HCV genotype 4 infection in patients in Rwanda. This regimen could be an effective treatment option in regions known to have a high prevalence of HCV genotype 4 of diverse non-a/d subtypes. Funding: Gilead Sciences.